People’s Campaign for Decentralised Planning and the Health Sector in Kerala - B. Ekbal
In spite of the economic backwardness, Kerala has made remarkable achievements in health almost compa- rable to that of even developed countries. The widely accepted health indicators like crude death rate, infant mortality rate, and life expectancy evidence this. (Table 1) Most analysts have seen Kerala’s achievements in health as something of an enigma. Kerala achieved the health status as par with that of USA spending roughly 10 US $ per capita per year while US spends about 3500 $ per capita per year on health care. The GDP of Kerala is even less than that of the National average. Kerala’s achievement in health in spite of its economic backwardness and very low health spending has prompted many analysts to talk about a unique “Kerala Model of Health,” worth emulating by other developing parts of the world